Message framing materials applied to healthy eating decision-making for pregnant women with gestational diabetes mellitus: An exploratory study - Xia Han; Nuo Xu; Sijing Chen; Jingjing Zhang; Ping Gu (PLoS ONE, 2025)
Aims To develop and initially validate message framing materials for promoting healthy dietary decisions in GDM populations. Methods The Delphi survey involved 17 experts, and consensus was obtained after two rounds. In Pre-survey I, 30 participants randomly selected one material (gain framing vs. loss framing) and complete a manipulation check item to ensure that the stimulus material manipulation was valid. Pre-survey II involved 60 participants who rated all messages using a Likert 5 rating questionnaire, a Wilcoxon signed rank sum test was used to examine the message framing effects. Results After two rounds of Delphi surveys, experts reached consensus on the final materials, which contained two message framings, each containing 11 entries. The manipulation test for materials achieved 100% validity. The findings indicated significant message framing effects on healthy eating decisions among GDM populations, with loss-framed messages proving more persuasive. Conclusion Scientifically valid message framing materials were developed and initially applied, providing an empirical basis and direction for future related research.